Common Standards for Professional Training of Future Border Guard Officers: Testing of Interoperability - Balendr, Andrii (Pedagogical Discourse, 2025)
The article reveals the features of the study to determine the level of interoperability of future border guard officers of the EU and Ukraine based on the implementation of common educational training standards, in order to use the acquired experience for the further integration of the Ukrainian border guard agency into the system of joint professional training of personnel of the border guard agencies of the EU countries. The experience of conducting a pan-European program for assessing the level of interoperability is considered, the implementation cycle of which includes the stages: updating, implementation, use and evaluation. The research methodology is based on the use of two main tools, namely: a questionnaire on the status of the implementation of the interoperability standard in national training programs addressed to border educational institutions of the EU member states and online testing addressed to future officers-graduates who studied under national training programs based on the interoperability standard. The proposed program is designed to assess the extent to which the Common Core Curriculum is integrated into the national basic training programs for border guards, as well as to determine the extent to which students have achieved competencies related to interoperability. In total, 566 participants from 22 border agencies of the EU member states and FRONTEX partner countries took part in the program. According to the first part, the level of implementation of the Common Core Curriculum topic in the training programs of educational institutions was determined. In the Ukrainian Border Guard Academy, it was 80%, while the average level among EU countries is 70%. According to the testing results, the Ukrainian cadets demonstrated a high level of success - 89%, which confirms the effectiveness of training border guards in Ukraine. The author analyzed the possibility of using this experience with the aim of implementing it into the professional training system of the personnel of the border agency of Ukraine.